Carbon and Oxygen Isotope Composition of Early Holocene Olivella Shell Beads from the Northwest Coast, USA. Issue 5 (13th September 2017) - Hadden, Carla S; Cherkinsky, Alexander; Smith, Geoffrey M; Ollivier, Aaron P; Pan, Hai
Abstract: Archaeological investigations of the age and origins of marine shell beads are important for understanding the emergence and maintenance of long-distance trade networks in prehistory. In this paper we expand upon and re-examine the incremental carbon ( 14 C and δ 13 C) and oxygen (δ 18 O) isotope data from two Olivella biplicata shell beads from the LSP-1 Rockshelter, Oregon, USA, to address two common problems in dating marine shell trade goods: (1) the source region is large, adding to uncertainty regarding the appropriate specification of ΔR; and (2) the 14 C activity within individual specimens is variable. Although this combination of factors severely limits the dating precision that is possible, we recommend a sampling and calibration approach that accounts for these added sources of uncertainty and minimizes the loss of precision. We recommend (1) sequential sampling in order to quantify the range of variability in 14 C within shells; (2) a Bayesian calibration procedure that models the 14 C dates as an ontogenetic sequence, in this case constrained by stable isotope sclerochronology; and (3) specifying ΔR in a manner that accounts for the full range of possible reservoir offsets in the source region.